Speech Technology Theory and Applications - Chen, Fang; Jokinen, Kristiina (Springer US : Imprint: Springer, 2010)
In recent years, spoken language research has successfully developed several practical applications, as well as brought forward advanced novel topics to investigate further. Speech Technology: Theory and Applications collects interesting research and development results and provides an overview of selected challenges still to be resolved. The book is organized along two main themes: research on enabling technology and applications that exemplify the use of this technology. Each chapter is an independent review of a specific topic, covering research problems and possible solutions. The basic technology development covers areas such as automatic speech recognition and speech synthesis, spoken dialogue systems and dialogue modeling, expressive speech synthesis, emotions and affective computing, multimodal communication and animated agents. The applications include speech translation, in-car, space, and military applications as well as those for special user groups. Discussion of general evaluation methodologies is also included. Speech Technology: Theory and Applications should be a useful reference for researchers, engineers and students in the field of speech technology.